2012
DOI: 10.1063/1.4751031
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of O-BN: A sp3-bonding boron nitride allotrope

Abstract: A fully tetrahedrally bonded boron nitride (BN) allotrope with an orthorhombic structure (O-BN) was investigated through first-principles calculations. O-BN has a bulk modulus of 371.8 GPa and a hardness of 66.4 GPa, thereby making it a superhard material with potential technological and industrial applications. O-BN becomes thermodynamically more stable than layered hexagonal BN (h-BN) at pressure above 1.5 GPa and is more favorable than the recently reported Pct-BN at any pressure. The phase transformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Therefore, BN is used for a wide range of industrial application with harsh environments such as high temperature ceramic composites [8,9]. All BN including wurtzite BN, cubic-BN, hexagonal BN (h-BN), and BN polymorphs [10][11][12][13][14][15] are insulators and remain insulating under high level compression [8]. More recently, Zhang et al [8] discovered that three-dimensional (3D) tetragonal BN becomes metallic, which is dynamically a stable phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BN is used for a wide range of industrial application with harsh environments such as high temperature ceramic composites [8,9]. All BN including wurtzite BN, cubic-BN, hexagonal BN (h-BN), and BN polymorphs [10][11][12][13][14][15] are insulators and remain insulating under high level compression [8]. More recently, Zhang et al [8] discovered that three-dimensional (3D) tetragonal BN becomes metallic, which is dynamically a stable phase.…”
Section: Introductionmentioning
confidence: 99%
“…There are 16 carbon atoms in C2/m phase and connect to each other through C-C bonds with a average length of 1.567 Å . It is slightly greater than diamond (1.535 Å ), Imma-carbon (1.555 Å ) [30], and P222 1 -carbon (1.412 Å ) at ambient pressure. The crystal structure of C2/m-carbon and M-carbon is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This Imma-carbon is a semiconductor with a direct band gap of 2.6 eV [28] with LDA and 4.17 eV [29] with HSE06. Furthermore, it has a high bulk modulus of 445 GPa [28] (440 GPa [29]) and a Vickers hardness of 83.5 GPa, which are much larger than that of c-BN (64 GPa [30] and 397 GPa [31]). Detailed analyses of the deformed atomic structures under tensile strain show that the lattice instability of Imma-carbon is due to the C-C bond break along the [010] direction.…”
Section: Introductionmentioning
confidence: 99%
“…For the vibration mode of a nearly flat band around 704 cm -1 , we found that it consists of three in-plane vibrations, i.e., B1-N2 along [ Many allotropes of BN structures have excellent mechanical properties. [37][38][39] For example, c-BN is the second hardest material known, inferior only to diamond. Since Hp-BN has a simple orthorhombic unit cell belonging to the P6 2 22 space group, the 9 independent elastic constants C 11 , C 22 , C 33 , C 44 , C 55 , C 66 , C 12 , C 13 and C 23 obtained at PBE level are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%